Assessment of mechanical engineering final year projects using fuzzy multi attribute utility theory - Dong, Chensong (HERDSA, 2012)
This paper presents an assessment method for the final year project theses of mechanical engineering students using Fuzzy Multi-Attribute Utility Theory (FMAUT). With the aid of FMAUT, the opinions of all the relevant staff members for thesis assessment are utilised to form an expert database. Final year theses are marked by two assessors using the current scoring rubric. The ratings given by the supervisor and assessor are conveniently converted into the final thesis mark with the aid of the developed approach, with the aim of reflecting the opinions of all the relevant staff members without increased workload. The advantages are increased clarities and reduced discrepancies. An example is given to illustrate the approach.